Photoinduced phase transitions - Nasu, K. (Keiichirō), 1946- (World Scientific, 2004)
A new class of insulating solids was recently discovered. When irradiated by a few visible photons, these solids give rise to a macroscopic excited domain that has new structural and electronic orders quite different from the starting ground state. This occurrence is called "photoinduced phase transition", and this multi-authored book reviews recent theoretical and experimental studies of this new phenomenon. Why and how do photoexcited few electrons finally result in an excited domain with a macroscopic size? How is the resultant photoinduced phase different from the ordinary thermal-induced phase? This review volume answers those essential questions